Integrative assessment of innovative agricultural products on soil functioning and quality - Malheiro, Catarina Correia de Lemos (2024)
In the mid-20th century, the development of the Green Revolution enabled the increase of agricultural production, which was essential to support a flourishing world population. Despite the increase in crop yields, this intensification has also led to ongoing ecosystem deterioration, imperilling the delivery of ecosystem services. Nowadays, crop yields are showing signs of stagnation while the available land for agricultural production is decreasing. Population projections estimate that the global population is expected to continue to rise, consequently reflecting higher food demand. To suppress this, agricultural products such as fertilizers are extensively used to enhance agricultural productivity, whose overuse and misuse are responsible for several environmental consequences. Research has been undertaken to tackle the much-needed development of innovative agriproducts to meet productivity demands, without compromising environmental integrity and human health. Nanofertilizers and organic fertilizers derived from insects (insect frass) are promising solutions to overcome these concerns. Still, to avoid further soil degradation, evaluating their efficacy and environmental safety is crucial. Aiming to contribute to this knowledge gap, this thesis's main goal was to evaluate the agronomic and environmental effects of two innovative fertilizer products, the nanofertilizer layered double hydroxide (LDH) and the organic fertilizer insect frass. The first approach consisted of the evaluation of the effect of two nanofertilizers, the Zn-Al-NO3 LDH and Mg-Al-NO3 LDH, on the avoidance behaviour of two soil invertebrate species, the enchytraeid Enchytraeus crypticus and the collembolan Folsomia candida, over a 3-month exposure period. Furthermore, the release of Zn and Mg from LDHs was evaluated. Results showed that enchytraeids were more sensitive to the LDH-treated soils and Zn-Al-NO3 LDH was considered less favourable compared to Mg-Al-NO3 LDH. The toxicity of the LDHs to the soil invertebrates decreased with time and was mainly related to the Zn and Mg release. Secondly, a chronic assessment was planned to evaluate the effects of both LDHs on the survival and reproduction of E. crypticus and F. candida over 3 months. It was shown that the toxicity of LDHs was species-dependent, with E. crypticus being more affected by Zn-Al-NO3 LDH and F. candida by Mg-Al-NO3 LDH. Contrary to the first approach, toxicity increased with ageing time, which was related to the availability of Zn and Mg in the soil pore water and the possible influence of other LDH constituents. Afterwards, the efficacy of Zn-Al-NO3 LDH as a potential alternative to conventional Zn fertilizers was evaluated using an approach that combined plant performance, soil functionality indicators and Zn fate assessments. This study showed that Zn-Al-NO3 LDH promoted a slow and controlled release of Zn, reflecting reduced Zn leaching. At the same time, a higher Zn content in the roots was observed, indicating an effective release of Zn, without causing toxicity to the plant development or the soil enzymes, whose activity is a proxy for soil function. In addition to LDHs, the efficacy and environmental safety of frass produced by black soldier fly (BSF) larvae were evaluated. On the one hand, an assessment was planned to evaluate the effects of BSF frass on the survival and reproduction of E. crypticus and F. candida, and on the early development of three plant species, the onion Allium cepa, the turnip Brassica rapa and the tomato Solanum lycopersicum. Overall, it was shown that BSF frass enhanced E. crypticus reproduction, while no effects were observed on the remaining endpoints of both invertebrate species. Seed germination was negatively affected at the highest application rate, and plants’ development was enhanced at intermediate application rates. Biological outcomes could be correlated to the changes in the soil's physical and chemical properties. On the other hand, a greenhouse experiment was conducted to evaluate the agronomic potential of frass for tomato production, combined with an environmental safety assessment. This approach included the evaluation of functional indicators that were grouped into ecosystem functions and assessed as ecosystem services. Briefly, results showed that BSF frass improved soil properties and tomato yield without changes in the morphology and physiology of the plants. No significant effects were observed on biotic factors, although a higher growth rate of aquatic macrophytes (in one sampling point) could indicate potential eutrophication processes. By condensing all measured functional indicators, this assessment showed that the BSF frass treatment promoted similar ecosystem multifunctionality as conventional fertilization treatments (a mixture of a mineral fertilizer with horse manure), highlighting this innovative fertilizer as a potential alternative to conventional fertilizers, known for causing environmental and human problems. The data generated in the present thesis displayed that both products can be considered potential new fertilization products under certain doses. Moreover, it is expected to contribute to improve the risk assessment of nanomaterials and organic fertilizers generated by insects.